Population transfer by stimulated Raman scattering with delayed pulses: the concept, some problems, and experimental demonstration - Bergmann, K; Schiemann, S; Kuhn, A (Publ by Int Soc for Optical Engineering, 1992)
We discuss recent progress in the attempt to gain complete control over the internal state population of atoms and molecules for collision dynamic studies and spectroscopy. We describe a method which relies on stimulated Raman scattering with pulses delayed in a counter-intuitive way. This method allows highly efficient transfer of population between atomic or molecular levels. It allows, in particular, selective population of highly excited vibrational levels.